ANALISIS EFISIENSI TEKNIS ANGGARAN BELANJA SEKTOR KESEHATAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2008-2010 - Nur Yatiman; Arif Pujiyono (Universitas Diponegoro, 2013)
This study aimes to analyze the technical efficiency of government budget spending on health sector at districts/cities in D. I. Yogyakarta in 2008-2010. Using the concept of technical efficiency based on production theory, the measurement of the efficiency value is obtained by using analytical methods Data Envelopment Analysis (DEA), which the DEA method the efficiency score obtained in this study of technical efficiency relatively. Based on similar research that ever held by Jafarov and Gunnarsson in 2008, the variable that use in this study are input variable and outcome variable, this research also uses the output intermediate variables. Calculating of technical efficiency score obtained in this study partially done by connecting each of these variables, so that in this study will be found score for technical efficiency and cost efficiency to technical systems. The results showed that generally most of the districts/cities in D. I. Yogyakarta in 2008-2010 is inefficient in technical health care cost. In 2010, the cost technical efficiency score at Sleman 42,14 percent, Bantul 39,18 percent, Gunung Kidul 53,57 percent, and two districts/cities that show 100 percent in cost technical efficiency score are Kulon Progo and Yogyakarta. This phenomenon indicates that not optimal yet in the management of health budget spending but not accompanied by the provision of facilities and health services for the society. Viewed the system technical efficiency, the generally most of the districts/cities in D. I. Yogyakarta done efficien and only Yogyakarta not yet efficien, but the system technical efficiency at Yogyakarta almost efficiency score. This condition reflect to based on analyzing the generally most of districts/cities in the using facilities and primary health care to get optimally the level of public health is efficien.